Pengembangan Motorik Halus pada Anak dengan Media Menggambar - Ade Fitriani; Elsa Maryana; Nadiya Rahmawati; Elsa Meilani; Vikri Haikal Ramdani; Dian Apriliani (Yayasan Inspirasi El Burhani, 2023)
Introduction: The development of children's fine motor skills greatly influences the development of children's skills so that they can improve their performance in the future. Objective: improve fine motor development in early childhood using the drawing method in Cibitung Girang village, Ciamis district. Method: The method used is observational with drawing and coloring media, and then as an evaluation material, the assessment is carried out by paying attention to the neatness of the pictures and colors. The activity was carried out on May 3, 2023, at RT. 04, R.W. 07, Cibitung Girang village, Ciamis district. Result: This community service activity was attended by 18 participants who were in early childhood. The activity took place smoothly and cooperatively. Conclusion: Drawing play therapy activities can improve fine motor development through holding, gripping, and moving a pencil. In addition, this therapy can control the child's emotions.